2004
DOI: 10.1046/j.1538-7836.2004.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of an immunologic polymorphism (D79H) in the heavy chain of factor V

Abstract: Summary. Background: During the study of a family with hereditary factor (F)V deficiency (FV Amersfoort, 1102 A > T in exon 7) we identified an individual with 5% FV heavy chain antigen (FV HC ) and 50% FV light chain antigen (FV LC ). Further testing revealed that apart from the FV Amersfoort allele a second variant FV allele was segregating in this family, which encodes for a FV molecule with a reduced affinity for mAb V-23 used in the FV heavy chain ELISA (ELISA HC ). Objective: Identification and character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The FV construct lacking the B-domain region from residues 828 to 1499 (FV des 827-1498) was made as described (30).…”
Section: Methodsmentioning
confidence: 99%
“…The FV construct lacking the B-domain region from residues 828 to 1499 (FV des 827-1498) was made as described (30).…”
Section: Methodsmentioning
confidence: 99%
“…The Asp79His change 36 recently reported to modulate FV levels in plasma 42 and, from expression and functional studies, to represent a neutral polymorphism 43 was detected in 5 subjects by sequencing of the exon 3. Screening for this polymorphism was extended to the whole population.…”
Section: Search Of New Determinants By Nucleotide Sequencingmentioning
confidence: 98%
“…Bossone et al [11] reported that it was associated with low FV levels and that it contributed to APC resistance, if FV Leiden was present on the other chromosome. Others did not observe decreased FV plasma levels [12,13] and could not find an associated risk of thrombosis [13]. Lunghi et al [14] observed a modulation of the effect of D79H on FV levels by the G/A polymorphism at position –426 in the promoter of the FV gene.…”
Section: Factor V Variations and Venous Thrombosismentioning
confidence: 99%